Effectiveness of nursing care centered in development in premature neonates compared with standard care - Cordero Méndez, Sara (2018)
Hospitalized preterm infants have higher risk of alterations in their neurodevelopment, that’s why it is essential to provide an integral approach that reduces these repercussions, especially from the nursing discipline, professionals responsible for the comprehensive care of these infants. Development-centered care is an optimal way to respond to these needs, involves easy-to-use care that promotes short-term and long-term neurodevelopment, decreases the costs of care with a shorter hospital length stay, and also involves and empowers parents in the care of their children. The objective of this article is to analyze the available scientific evidence regarding the effectiveness of nursing care focused on development compared with standard care to reduce long- term complications in hospitalized preterm infants. Clinical practice based on evidence was used as methodology, initially a prognostic type clinical question was posed and the objectives according to this were raised, based on which a set of descriptors were identified. Subsequently, scientific evidence was searched in different scientific databases.